Alexander Blok in the Russian Environment of Interwar Wilno - Lavrinec, Pavel (Literatūra, 2021)
The study of the significance of Alexander Blok and his work in the perceptions of the Russian environment in the interwar Wilno reveals its literary orientations. Blok’s literary reputation was supported and strengthened by the main sources and processes of the formation of literary reputation – Blok’s text themselves (in particular, books in the library of the Vilna Russian society and reprints from Soviet publications), evaluations of his work in the Wilno press, literary evenings and discussions dedicated to his poetry. The research materials were collected from the Wilno press in Russian language published in 1921–1939. The study shows the exceptional importance of Blok, as the greatest poet of the era, in the perceptions of the Russian community.
Keywords: Alexander Blok; Dorofey Bokhan; Wilno; literary hierarchy; Russian Periodicals; Russian Diaspora; 20th century Russian poetry